Nonlinear digital filters : analysis and applications - Ling, Wing-Kuen (Academic, 2007)
This book provides an easy to understand overview of nonlinear behavior in digital filters, showing how it can be utilized or avoided when operating nonlinear digital filters. It gives techniques for analyzing discrete-time systems with discontinuous linearity, enabling the analysis of other nonlinear discrete-time systems, such as sigma delta modulators, digital phase lock loops and turbo coders. Features:. Uses new methods based on symbolic dynamics, enabling the engineer more easily to operate reliable nonlinear digital filters. Gives practical, 'real-world' applications of nonlinear digital.